Analysis of status and influencing factors of knowledge, attitudes, and expectations towards assisted reproductive technology among infertile women in Lebanon: A cross-sectional study - Reva Mosleh; Hiba Assi; Jana Kassir; Hassan Ajami; Joseph Azoury; Roula Ajrouche; Amal Al-Hajje (PLoS ONE, 2026)
Background Infertility affects millions globally, and while assisted reproductive technology (ART) has become a cornerstone of its treatment, there is limited research on how Lebanese women perceive these services. This study aims to fill the gap by assessing each of the knowledge, attitudes, and expectations of Lebanese women experiencing difficulty conceiving towards ART. Methods A cross-sectional study was conducted between June and September 2024, involving 346 Lebanese women from two fertility centers in Beirut. Participants were selected by simple random sampling to complete the questionnaire through individual interviews. Descriptive and bivariate analyses were performed, and generalized linear models were used to explore the associated factors of knowledge, attitudes, and expectation scores. Results The results showed that 56.4% of participants had good knowledge, 54.9% had positive attitudes, and 73.7% exhibited high expectations. The generalized linear models revealed that previous ART use (β = 0.151), receiving ART information from a doctor (β = 0.064), female age (β = 0.005), and physical exercise (β = 0.119) were linked to higher knowledge, while higher family income (β = −0.133), history of immunodeficiency (β = −0.275), living in centers (β = −0.066), were linked to lower knowledge. For attitudes, residing in South Lebanon (β = 6.136), having a history of ovarian cyst removal (β = 2.065), receiving ART information from a doctor (β = 1.151) and female age (β = 0.120) were linked to positive attitudes, while living in centers (β = −1.835), having a regular menstrual period (β = −1.521) were linked to lower attitudes. For the expectations, female hormonal disorder (β = 2.758) was significantly associated with higher expectations, while advanced female age (β = −0.768) was associated with lower expectations. Conclusion This study identifies associated factors influencing knowledge, attitudes, and expectations toward ART. To optimize these aspects, interventions should focus on effective education, personalized treatments, reducing barriers, and providing psychological support to improve women’s reproductive health. Further research is needed to explore these factors in the broader population.